Influences of Playing Position and Quality of Opposition on Standardized Relative Distance Covered in Domestic Women's Field Hockey: Implications for Coaches. Issue 6 (June 2018) - Vinson, Don; Gerrett, Nicola; James, David V. B.
Abstract : Abstract: Vinson, D, Gerrett, N, and James, DVB. Influences of playing position and quality of opposition on standardized relative distance covered in domestic women's field hockey: Implications for coaches. J Strength Cond Res 32(6): 1770–1777, 2018—The purpose of this study was to compare the standardized relative distance covered by the various playing positions (defenders, midfielders, and forwards) against different quality of opponents in domestic women's field hockey. Data were collected from 13 individuals competing for 1 team in the English Premier League across an 18-game season. Data were collected using portable global positioning system technology. Distance data were grouped into 6 speed zones relative to individual players' maximum sprint speeds and then standardized by dividing by the number of on-pitch minutes. Dependent variables included distance covered in the 6 speed zones, as well as the number of sprints and repeated sprint efforts (RSEs) completed in the highest speed zone. Participants covered a significantly greater total distance when competing against opponents from top 3 teams compared with middle 3 teams (111.78 ± 2.65 m·min −1 vs. 107.35 ± 2.62 m·min −1, respectively). This was also true for distance covered in zone 4 (running) (29.47 ± 1.69 m·min −1 vs. 27.62 ± 1.45 m·min −1, respectively) and zone 5 (fast running) (23.42 ± 1.76 m·min −1 vs. 21.52 ± 1.79 m·min −1, respectively). Defenders (99.77 ± 4.36 m·min −1 ) covered significantly less total meters per minute than midfielders (117.20 ± 4.36 m·min −1 ) and completed significantly fewer RSEs per on-pitch minute (0.21 ± 0.03 and 0.33 ± 0.03, respectively). Midfielders covered significantly less distance in zone 2 (walking) than forwards (19.38 ± 1.64 m·min −1 and 30.33 ± 2.12 m·min −1, respectively). Conversely, midfielders were shown to cover significantly more distance in zone 3 (jogging) than forwards (32.84 ± 1.10 m·min −1 and 24.61 ± 1.42 m·min −1, respectively). A standardized and relative assessment may be useful for coaches' and performance analysts' understanding of players' performance in different positions or against different quality opponents.